2019
DOI: 10.1111/tid.13185
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia and renal dysfunction due to intravesical cidofovir for virus‐associated hemorrhagic cystitis after kidney and allogenic hematopoietic stem cell transplantations

Abstract: Virus-associated hemorrhagic cystitis (VAHC) is a common and lifethreatening complication of allogenic hematopoietic stem cell transplantation (allo-HSCT), occurring in 8%-27% of allo-HSCT recipients with severe hematuria. 1 Late onset hemorrhagic cystitis (HC) in the post-engraftment period is associated with an adenovirus (ADV), a BK polyomavirus (BKPyV), or a JC polyomavirus (JCPyV) infection. Hemorrhagic cystitis may cause significant morbidity, prolonged hospital stay, and increased mortality. Risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[15] However, few cases of acute nephrotoxicity have still been reported after cidofovir EV. [18,19] In a pharmacokinetic analysis in 6 adult patients with BKPyV or adenovirus HC, Aitken et al reported that, compared with the reported AUC0−24 for an equivalent IV dose, EV instillation of cidofovir (given at a dose of 2.5 to 5 mg/kg over 30 to 120 min of clamp time) resulted in a 1% to 74% (median 4%) of the corresponding systemic exposure. [18] Thus, although the risk of renal insufficiency seems much lower with EV compared to IV administration, this risk is not completely zero and we recommend to monitor the renal function and to remain cautious, particularly in vulnerable patients with renal comorbidities or nephrotoxic co-medications.…”
Section: Discussionmentioning
confidence: 99%
“…[15] However, few cases of acute nephrotoxicity have still been reported after cidofovir EV. [18,19] In a pharmacokinetic analysis in 6 adult patients with BKPyV or adenovirus HC, Aitken et al reported that, compared with the reported AUC0−24 for an equivalent IV dose, EV instillation of cidofovir (given at a dose of 2.5 to 5 mg/kg over 30 to 120 min of clamp time) resulted in a 1% to 74% (median 4%) of the corresponding systemic exposure. [18] Thus, although the risk of renal insufficiency seems much lower with EV compared to IV administration, this risk is not completely zero and we recommend to monitor the renal function and to remain cautious, particularly in vulnerable patients with renal comorbidities or nephrotoxic co-medications.…”
Section: Discussionmentioning
confidence: 99%